Transitioning youth with autism spectrum disorders and other special health care needs into adult primary care: A provider survey. (April 2021) - Ames, Jennifer L; Massolo, Maria L; Davignon, Meghan N; Qian, Yinge; Cerros, Hilda J; Croen, Lisa A
Health care continuity during the transition from pediatric to adult care is critical to helping individuals with autism spectrum disorders manage complex medical and psychiatric co-morbidities that start in childhood and evolve with age. We conducted a brief online survey of pediatric and adult providers at Kaiser Permanente Northern California, a large integrated health care delivery system, to assess departmental policies and personal approaches to transitioning patients with special health care needs, including autism spectrum disorders. A total of 354 pediatric (43% response rate) and 715 adult providers (30% response rate) completed the survey. A large majority of departments did not have transition policies in place. Many providers in both primary care and mental health did not provide transition resources, review legal changes, use standardized assessment tools, or communicate with the next/previous provider. Transition planning was usually delayed until age 17 or later. Most providers did not have consistent approaches to the transition of care for youth with special health care needs and may be inadequately prepared to handle the process for patients with autism spectrum disorders. As the population of transition-age youth with autism spectrum disorders continues to grow, there is urgent need to understand how to best implement transition policies that promote early communication between providers and families and track outcomes among transitioning patients with special health care needs. Lay Abstract: The transition from pediatric to adult care is a critical inflection point for the long-term health of youth with autism spectrum disorders and other special health care needs. However, for many patients, their caregivers, and providers, the transition lacks coordination. This survey study demonstrates that pediatric and adult providers struggle to implement many components of transition best practices for youth with autism and other chronic conditions, highlighting the urgent need for enhanced medical coordination and additional transition training and resources.